Pemanfaatan Arang Aktif Tempurung Kemiri (Aleurites moluccana L. Willd) Sebagai Adsorben Zat Warna Naphtol - Hamu, Gustafianus Velgi Hamu V; Gauru, Imanuel; Kadang, Luther (Chemistry Notes, 2023)
It has been conducted a study about the utilization of candle nut shell coal (aleurites moluccana L. Willd) as adsorbent for naphtole dye, which it aims to know the characteristics of optimum condition covering pH, contact time, and adsorption consentration, along with the adsorption capacity of candle nut shell active coal (Aleurites moluccana L. Willd) against naphtole dye. The characteristics determination of candle nut shell active coal was done by identification of functional groups using FTIR. The determination of surface area, porous volume and porous size using SAA. The characteristics result using FTIR exhibited that the coal before and after activation contains functional groups of –OH, Csp3-H, CH2, CH3, CO Eter, aromatic C=C, and aromatic C-H. while, characterization using SAA showed the active coal surface area obtained is 17,20 m2/g with porous voleme is 0,021 mL/g and porous size is 1,60 nm. The optimum condition of adsorbent in adsorbing naptol dye is 60 ppm, takes place at pH 5 with contact time of 120 minutes. The adsorption capacity measure result of candle nut active coal obtained is 3,850 mg/g. adsorption process of naphtole dye follows Langmuir isotherm with R2 is 0.8939 and adsorption energy is 99,942 Kj/mol.